Modern Methods of Diagnosis and Treatment of Diseases of Peripheral Arterial Vessels (Eurasian Medical Research Periodical, 2023)
The overall prevalence of peripheral artery disease (PAD) or chronic obliterative arterial disease of the arteries of the extremities is 3+10% reaching 15 -20% among patients older than 10 years. A special feature of the PAD is the tendency to a steady progression of the process with a high frequency of amputations, disability, and lethality. As a result, the average life expectancy of these patients is about 10 years less than in people without signs of PAD.